Sustainable-entrepreneurs: quantifying opportunities and social networks, case study on sustainable entrepreneurs in a heavy industrial area. (2017) - Boutillier, Sophie; Ryckelynck, Philippe
Our objective is to study the capacity of innovation of craft enterprises in a 'poor' territory in a particular sector (sustainable technologies) through a case-study on 50 entrepreneurs located in Dunkirk (France). The analysis of appropriate Boolean statistical characters reveals the balance between the various kinds of resources, and the key role of (informal) social networks of the entrepreneurs in gathering resources which are required to manage the projects.